Increased risk of valvular heart disease in patients with ankylosing spondylitis: a nationwide population-based longitudinal cohort study. (June 2021) - Siao, Wun-Zhih; Liu, Chin-Hsiu; Wang, Yu-Hsun; Wei, James Cheng-Chung; Jong, Gwo-Ping
Aims: We aimed to evaluate the risk of valvular heart disease (VHD) among patients with ankylosing spondylitis (AS). Methods: This was a population-based cohort study utilizing the Longitudinal Health Insurance Research Database of the National Health Insurance in Taiwan. Patients with and without coding of newly diagnosed AS from 1999 to 2013 were assigned to the AS and non-AS groups, respectively. Primary outcome was the incidental risk of VHD. Multiple Cox regression was used to estimate the adjusted hazard ratio of VHD. Subgroup analysis and sensitivity tests were also conducted. Results: The AS group included 3780 patients, and 22, 680 matched subjects without an AS diagnosis were identified as controls. The AS group had an increased risk of VHD compared with non-AS controls (adjusted hazard ratio: 1.63; 95% confidence interval: 1.43–1.86; p < 0.001). Subgroup analysis also revealed an increased risk of individual types of VHD, including aortic, mitral, and tricuspid valve disease. Patients in the AS group had a higher incidence of valve replacement surgery after the onset of VHD. Conclusion: Patients with AS had a significant risk of VHD compared to non-AS controls in this population-based cohort study. Screening for VHD may be needed in caring patients with AS. We suggest that echocardiography may be performed when patients are diagnosed with AS.